The Chinese from Indonesia in the Netherlands and their heritage; Chinese Indonesian Heritage Center (CIHC) - Liem, Patricia Tjiook (UI Scholars Hub, 2017)
Chinese from Indonesia in the Netherlands are (post)colonial migrants who share a long historical tie with the Dutch. In this article the author brings together and focuses on three interconnected subjects: Chinese from Indonesia in the Netherlands; the historical development and present meaning of